Treatment of Intestinal Inflammation With Epicutaneous Immunotherapy Requires TGF-β and IL-10 but Not Foxp3+ Tregs - Chen, Xin; Berin, M. Cecilia; Gillespie, Virginia L.; Sampson, Hugh A.; Dunkin, David (Frontiers in Immunology, 2021)
Background: Inflammatory bowel disease (IBD) involves an increase in T effector cells in the intestines that disrupts the normal balance with T regulatory cells (Tregs). A therapy that restores this balance has the potential to treat IBD. We have shown that epicutaneous exposure to OVA induces Tregs that are able to induce tolerance. The Tregs also migrate to the intestines where they alleviate colitis in mice, demonstrating the potential for skin induced Tregs to treat intestinal inflammation. We investigated the role of Foxp3, IL-10 and TGF-β in the suppression of colitis by epicutaneous immunotherapy (ET). Methods: RAG1-/- mice were transferred with CD4+CD45RBhi T cells from wild type mice to induce colitis. To determine whether Foxp3+ Tregs, IL-10- or TGF-β-producing Tregs were necessary, Foxp3-DTR, IL-10-/- or CD4-dnTGFBRII mice were immunized with OVA and OVA TCR enriched T cells were added. As control groups, some mice were given OVA TCR enriched T cells from wild type mice or no OVA TCR enriched T cells. Half of the mice in each group were then exposed on the skin to Viaskin patches containing OVA weekly for 3 weeks. Mice given OVA TCR enriched T cells from Foxp3-DTR mice were given diphtheria toxin (DT) or not in addition to ET. Mice were assessed for weight loss, colon length, colonic cytokine production and histological inflammation. Results: ET, after injection with memory T cells derived from wild type mice, prevented weight loss, decreased colonic inflammatory cytokine production and histological colitis. ET in the absence of the memory T cells did not alleviate colitis. ET, after injection with memory T cells derived from Foxp3-DTR mice, prevented weight loss, decreased colonic inflammatory cytokine production and histological colitis. Ablation with DT did not impair the ability of ET to alleviate colitis. ET failed to alleviate colitis when OVA TCR enriched T cells were derived from IL-10-/- or CD4-dnTGFBRII mice. Conclusions: ET through induction of Tregs, which produce IL-10 and TGF-β, could be a promising treatment for IBD.